Respond to this Question
Similar Questions

Maths
given (e^x)sin3x = Im((e^x)(e^i3x)) Integrate (e^x)sin3x.dx You can just take the imaginary part of the integral of ((e^x)(e^i3x))= e^([3i +1)x] which is IM(3i +1)e^(3ix + x) = IM (3i +1)e^x*e^(3ix) = IM {(3i +1)*e^x* [ cos (3x) + … 
maths
If (e^x)(sin3x)=Im ((e^x)(e^i3x)) integrate (e^x)(sin3x) I get the answer(e^x)(cos3x3sin3x) +C My book gets the answer (1/10)(e^x)(sin3x3cos3x)+C Can any explain which answer is right and why Integral of e^(1+3i)x = e^(1+3i)x /(1+3i) … 
Calculus part 3 so sorry
y = e^2xsin3x Find the derivative. So I used the product rule and I got sin3x(e^2x)+cos^3x(e^2x). But the actual answer is sin3x(2e^2x)+cos^3x(3e^2x) Where the the 2 and 3 before the e come from? 
maths
Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic factors; deduce that cos3x = 4[cos(x) cos(pi/6)][(cos(x) cos(pi/2)][(cos(x) cos(5pi/6)] 
maths
Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic factors; deduce that cos3x = 4[cos(x) cos(pi/6)][(cos(x) cos(pi/2)][(cos(x) cos(5pi/6)] 
maths
prove that cos3x+sin3x/cos xsin x=1+2sin2x 
math
Solve sin2x + sin4x = cos2x + cos 4x for x in the interval[0,2pi) Hint: the following substitution should come in handy: sin3x= cos3x . tan3x 
pre calc
(cos3x)^2+(sin3x)^2=cos(f(x)) find f(x) 
precalc
(cos3x)^4+(sin3x)^4=cos(g(x)) find g(x) 
precalc
(cos3x)^4+(sin3x)^4=cos(g(x)) find g(x)